Antibacterial effect of Melastoma malabathricum leaves extract against locally isolated bovine mastitis pathogens - Tan, Y.J.; Koh, S.P.; S., Khozirah; M., Rozaihan; M., Jacob; N.A.W., Khirrol; M.S., Mohd-Shaharizan; Tan, G.H. (Rynnye Lyan Resources, 2024)
Mastitis is the most frequently diagnosed disease in dairy cattle and responsible for the major economic losses. To date, antibiotics are the most common treatment for this disease. However, the use of antibiotic was reported to be the main contributor to milk contamination and frequent use of this therapy will lead to microbial antibiotic resistance. Furthermore, the antibiotic withdrawal time and mastitis therapy will cause a huge profit loss to dairy farmers. Therefore, alternative plant-based treatments should be explored to replace the use of antibiotics. The aim of this study was to evaluate the antibacterial activity of Melastoma malabathricum (MM) extract against eight common bovine mastitis pathogens isolated from a local commercial dairy farm, namely Staphylococcus aureus (SA), Staphylococcus chromogenes (SC), Staphylococcus haemolyticus (SH), Streptococcus uberis (SU), Streptococcus agalactiae (RK3C), Pseudomonas aeruginosa (PA), Klebsiella pneumoniae (HS09A) and Escherichia coli (GN9B). MM aqueous extracts showed antibacterial activities against all pathogens, with RK3C having the highest antibacterial efficacy at an effective extract concentration of 3.12 mg/mL, followed by SA (6.25 mg/mL), SU (6.25 mg/mL), SH (12.5 mg/mL), PA (12.5 mg/mL), GN9B (12.5 mg/mL), SC (50 mg/mL), and HS09A (50 mg/mL). Most of the pathogens (SA, SH, SU, RK3C and PA), especially Gram-positive bacteria were killed within the half hour when incubated either with 25 or 50 mg/mL concentration of MM aqueous extract. In this study, the results demonstrated bactericidal effect of the MM extract against all pathogens, reflecting the potential of MM aqueous extract as new antibacterial agent against bovine mastitis pathogens.